Presence of generalized periodic discharges and hospital mortality - MIYASHIRO, Larissa; OLIVEIRA DE PAULO, Carolina; TWARDOWSCHY, Carlos Alexandre (Arquivos de Neuro-Psiquiatria, 2020)
Background: Generalized periodic discharges (GPDs) are rare patterns that can be found in long-term electroencephalographic monitoring in critical patients. These patterns have been correlated with non-seizure crisis and non-convulsive status epilepticus, associated with poor prognosis. Objective: To compare the outcome between patients who developed GPDs and patients with other abnormalities in long-term electroencephalographic monitoring. Methods: A retrospective study was performed by analyzing the medical records of 112 patients over 18 years who developed GPDs during long-term electroencephalographic monitoring (12–16 hours of monitoring) in the intensive care unit of a general hospital, compared with a group that had only nonspecific abnormalities in the monitoring. Results: Age and cardiorespiratory arrest (CA) were risk factors for death - OR 1.04 (95% CI 1,02 - 1,07) and p<0.001; OR 3.00 (95% CI 1,01 - 8,92) and p=0.046, respectively. It was not possible to evaluate if GPDs alone were associated with an unfavorable outcome or would be a bias for the development of CA in these patients. However, of the six isolated GPDs cases, 2/3 evolved to death, showing a tendency to worse prognosis. A significant difference (p=0.031) was observed for a worse outcome when comparing the group of 28 patients who presented GPD or CA with the other group which did not present any of these variables; of these 28 patients, 20 (71.4%) died. Conclusions: The presence of post-CA GPDs was associated with worse prognosis, but it was not clear whether these patterns are independent factors of an unfavorable evolution.
Keywords: Electroencephalography; Intensive Care Units; Encephalopathies; Hospital mortality